Employment and Societal Changes in Iraq Challenges and Policies (Journal of the College of Education for Women, 2019)
This study attempts to focus on there lation ship between employment policies andsocietal changesinIraq.Theconstruction ofoperational policyincommunitiesin crisis remains fraught with challenges and risks, especially in countries that have longoutstanding conflict sand crises, it is important in this context to achieve those policy and build the foundations of human security and poverty alleviation, unemployment, to find effective ways to help the community to achieve stability and reduce the risk of renew edorrepeat the cycleofviolence-butthatwouldrequirearadicalrethinking, including rethinking the way evaluating therisksandchallengesand management.And thatsuchaprojectshouldbe based ona clear roadmap, andthevisionsofdevelopmentanda clearandeffective. This studymay contribute tolaying the foundation forother studieshelp buildfuture scenariosenablespartnersin development of access to better options for sustainable development.